Parental and familial involvement in the school community - Roth, Rachel (My University, 2015)
Parental/familial involvement in the classroom as well as school community is an issue of constant importance. Parents and families are crucial participants in a child's education. It is critical to create a bridge between home and school. Parental/familial involvement within the school community is essential to the quality of all children's educational as well as their cognitive, physical, emotional, and social development. This Action Research Project was focused on finding the most effective means of getting parents/families involved in the school community. This study was completed at a small private Montessori children's house school we will call "Children's House" Montessori in the Midwest. 22 families were involved in this Action Research Project. This study used surveys after each community event/involvement activity occurred. The surveys were sent to every family to measure the effectiveness of the event or information provided in helping the parents/families get involved in the school community. Results indicated that each community building activity or parent communication helped the parents and families feel more connected to the school community. The surveys given helped to decipher which activities and communications were most important to the parents and families.
Plan B Paper. 2015. Master of Science in Education- Montessori--University of Wisconsin-River Falls. Teacher Education Department. 65 leaves. Includes bibliographical references (leaves 32-33).
Keywords: Early childhood education--Parent participation; Montessori method of education